The remote brief intervention and referral to treatment model: Development, functionality, acceptability, and feasibility. (1st October 2015) - Boudreaux, Edwin D.; Haskins, Brianna; Harralson, Tina; Bernstein, Edward
Highlights: A telehealth model for brief substance use interventions was designed. The service provides interventions for both alcohol and drug use. Several possible implementation strategies were identified by end-users. Strategies involving consultation during the medical encounter engaged patients. Strategies that called the patient after the encounter did not engage patients. Abstract: Background: Screening, brief intervention, and referral to treatment (SBIRT) is effective for reducing risky alcohol use across a variety of medical settings. However, most programs have been unsustainable because of cost and time demands. Telehealth may alleviate on-site clinician burden. This exploratory study examines the feasibility of a new Remote Brief Intervention and Referral to Treatment (R-BIRT) model. Methods: Eligible emergency department (ED) patients were enrolled into one of five models. (1) Warm Handoff: clinician-facilitated phone call during ED visit. (2) Patient Direct: patient-initiated call during visit. (3) Electronic Referral: patient contacted by R-BIRT personnel post visit. (4) Patient Choice: choice of models 1–3. (5) Modified Patient Choice: choice of models 1–2, Electronic Referral offered if 1–2 were declined. Once connected, a health coach offered assessment, counseling, and referral to treatment. Follow up assessments were conducted at 1 and 3 months. Primary outcomes measured were acceptance, satisfaction, and completion rates. Results: Of 125 eligible patients, 50 were enrolled, for an acceptance rate of 40%. Feedback and satisfaction ratings were generally positive. Completion rates were 58% overall, with patients enrolled into a model wherein the consultation occurred during the ED visit, as opposed to after the visit, much more likely to complete a consultation, 90% vs. 10%, χ 2 (4, N = 50) = 34.8, p < 0.001. Conclusions: The R-BIRT offers a feasible alternative to in-person alcohol SBIRT and should be studied further. The public health impact of having accessible, sustainable, evidence-based SBIRT for substance use across a range of medical settings could be considerable.